Hepatoprotective and Antidyslipidemia Effect of Jatropha Tanjorensis Leaf Extract in Isoprenaline Induced Myocardial Infarction in Albino Rats (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Recently, there is an increase in the incidence of myocardial infarction which manifest as a result of disrupted blood supply and oxygen to the myocardium.Objective: This study assessed the protective outcome of methanol extract of Jatropha tanjorensis leaf on liver function biomarkers and lipid profile condition in the isoprenaline induced myocardial infarction in albino rats.Methods: Thirty six (36) rats were divided at random into six (6) groups of six rats per group. Group 1 was normal control, group 2 was negative control (85mg/kg of isoprenaline only), group 3 positive control (pretreated with 2mg/kg carvedilol for 28 days), group 4 through 6 were pretreated with 200mg/kg, 400mg/kg and 600mg/kg of methanol leaves extract of Jatropha tanjorensis respectively for 28 days.Results: The extract at 200mg/kg and 400mg/kg significantly (p